Effect of heat treatments on microstructural evolution of additively manufactured and wrought 17-4PH stainless steel. (15th October 2018) - Sun, Yu; Hebert, Rainer J.; Aindow, Mark
Abstract: Additively manufactured (AM) components usually have nonequilibrium microstructures. Post-built heat treatments are recommended for AM components to achieve homogenous microstructures. In this study, the effects were investigated of conventional solutionizing and precipitation hardening (H-900) heat treatments on the microstructure evolution of 17-4PH AM and wrought components. Microstructural characterization techniques including SEM, TEM and EBSD analysis were used on 17-4PH AM and wrought components to obtain quantitative information about the microstructure and phase evolution during these heat treatments. These microstructural studies demonstrate that 17-4PH AM components can achieve microstructures and hardnesses similar to those of wrought samples by post-built heat treatments. Graphical abstract: Highlights: As-built 17-4 PH has steel an inhomogeneous columnar microstructure composed of ferrite, martensite, and some austenite. Solution heat treatments homogenized the grain structure and eliminated the {100} texture observed in as-built samples. Oxide inclusions pinned grain boundaries during heat treatment thereby refining the grain structure. Precipitation heat treatment yielded Cu-rich nano-precipitates without further changes in the grain structure. Heat treatments can achieve comparable microstructures and hardness in additively manufactured and wrought 17-4 PH samples.